Decoding the genome of Bacillus thuringiensis subsp. israelensis VCRC B668 to understand its mosquitocidal potential for biopesticide development - Jibi Lukose; A. Mathivanan; Bhavna Gupta; Sahadiya Mandodan; V. Abhisubesh; Kakhuangailiu Gangmei; Bhagyashree Bora; Aneha Kunnikuruvan; P. Hemaladkshmi; I. Geetha; S. Poopathi; R. Paramasivan (Brazilian Journal of Microbiology, 2026)

A Terrain-Corrected Dynamic NDSI Framework Integrating C-Correction and Adaptive Thresholding for Improved Snow Cover Mapping in the Himalayas - Deva Jefflin Aruldhas; Chandre Gowda Cheluvegowda; Geetha Priya Murugesan; Charu Prabha Rajasekaran Palanikumar; Sushil Kumar Singh; Anil V. Kulkarni (Journal of the Indian Society of Remote Sensing, 2026)

Plant Probiotics Modulate Physio-biochemical Characteristics of Vigna Radiata Cultivars Under Polyethylene Glycol Induced Drought Stress - Vinoth Kumar Muniyappan; K. Sundaralingam; U. Sivakumar; V. Vijaya Geetha; T. Murugeshwari (Journal of Soil Science and Plant Nutrition, 2026)

Seismic fragility assessment of reinforced concrete bridges: a comprehensive review of methodologies, isolators, and soil structure interaction - Ashwini Satyanarayana; Dushyanth V. Babu R; H. M. Sheethal; L. Geetha (Innovative Infrastructure Solutions, 2026)

Valorizing of mulberry silkworm (Bombyx mori L.) frass as a nitrogen fertilizer on growth and economic attributes of tomato (Lycopersicon esculentum Mill.) - K. Elango; V. Dhinesh; V. Divyabharathi; S. Abinandhan; K. S. Chenduran; C. Dineshkumar; V. C. Geetha (Agroforestry Systems, 2026)

Thermal Conversion of Sugarcane Bagasse to Biochar and Its Application in Treatment of Methylene Blue Contaminated Water - T. Geetha; John K Smitha; Litty Mathew Irimpan; Manju Sebastian; V. Geetha; C. J. Theresa; Bincy Joseph; M. Nancy; K. Nimmy (Sugar Tech, 2026)

Correction to: Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

The Effect of Moringa Powder Supplementation on Quality of Sleep in a Patient of Long COVID-19 syndrome Insomnia with Pre-Existing Erythema Nodosum – A Case Report - Manjunath Rajanna; Geetha Kumari V (Sleep and Vigilance, 2025)

Effects of sampling methodology on phenology indices: Insights from sites across India and modelling - Yadugiri V Tiruvaimozhi; Karthik Teegalapalli; Abinand Reddy; Akhil Murali; Aparajita Datta; Aparna Krishnan; Jayashree Ratnam; Mahesh Sankaran; Shasank Ongole; Srinivasan Kasinathan; TR Shankar Raman; Geetha Ramaswami (Journal of Biosciences, 2025)

Cisgenics–An advanced breeding technique for Fruit crop amelioration - V. Boomika; M. S. Aneesa Rani; K. S. Vijai Selvaraj; P. Irene Vethamoni; R. Kalaiyarasi; P. Geetha (Euphytica, 2025)

Management of Diverse Weed Flora in Widely Spaced Sugarcane Plant Crop in Tropical India Through Sequential and Tank Mix Application of Herbicides - S. Anusha; P. Geetha; V. Krishnapriya; A. S. Tayade; R. Arun Kumar (Sugar Tech, 2025)

The Aegilops ventricosa derived 2NvS translocation for enhanced defense against multiple diseases in wheat - R. Nisha; P. Shajitha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; Shailendra Jha; Niharika Mallick; Rajbir Yadav; S. C. Bhardwaj; O. P. Gangwar; S. Vijaishree; M. Geetha; et al. (Journal of Crop Science and Biotechnology, 2025)

Advanced landslide susceptibility mapping and analysis of driving mechanisms using ensemble machine learning models - Mashael Maashi; Nada Alzaben; Noha Negm; V. Venkatesan; S. Sabarunisha Begum; P. Geetha (Journal of South American Earth Sciences, 2025)

Parametric evaluation and prediction of design parameters of geofoam using artificial neural network and extreme gradient boosting models - Parvathi Geetha Sreekantan; Aali Pant; G. V. Ramana (Innovative Infrastructure Solutions, 2024)

Quinoline-quinoline schiff-base as an effective chromogenic, fluorogenic, and smartphone assisted RGB detection of Pb2+ ion in near aqueous medium - Kathirvel R; Poongodi M; Vetriarasu V; Vivekanandan K.E; Selvakumar K; Sami Al Obaid; Arivalagan Pugazhendhi; Geetha Venkatesan (Environmental Research, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Mineral magnetic properties of ultisol profiles from tropical southern India - Mohan Reethu; Kizhur Sandeep; Joju G. Sebastian; Anish K. Warrier; Geetha H. Aravind; Abdul K. Rafaz; Jithin Jose; Radhakrishnan Akshay; Vadakkath V. Suhaiba (Geosciences Journal, 2023)

Neisseria montereyensis sp. nov., Isolated from Oropharynx of California Sea Lion (Zalophus californianus): Genomic, Phylogenetic, and Phenotypic Study - Dmitriy V. Volokhov; Tatiana A. Zagorodnyaya; Vyacheslav A. Furtak; Geetha Nattanmai; Linnell Randall; Sherly Jose; Yamei Gao; Frances M. Gulland; Tobias Eisenberg; Pierluigi Delmonte; Jochen Blom; Kara K. Mitchell (Current Microbiology, 2023)

Biochemical profiling of ‘toko’ (Livistona jenkinsiana griff.): An endangered underutilized fruit of north east India - T. Yatung; V. Bhargav; K.S. Shivashankara; G.A. Geetha; A.N. Lokesha (Biochemical Systematics and Ecology, 2023)

Development of in vitro pollen germination protocol for recalcitrant triticale pollen (X Triticosecale Wittmack) - P. Jayaprakash; John Peter; P. Shajitha; V. Balaji; R. Nisha; M. Geetha; V. K. Vikas; M. Sivasamy (Cereal Research Communications, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Studies on the partial characterization of extracted glycosaminoglycans from fish waste and its potentiality in modulating obesity through in-vitro and in-vivo - Geetha V; Moumita Das; Mehrdad Zarei; Mayookha VP; Nanishankar V Harohally; Suresh Kumar G (Glycoconjugate Journal, 2022)

Techno-economic evaluation of Asian seabass (Lates calcarifer) nursery rearing in small net cages (hapas) under different coastal salinities - M. Kumaran; K. P. Kumaraguru Vasagam; R. Subburaj; P. R. Anand; K. Ramachandran; R. Geetha; D. Deboral Vimala; R. Anandaraja; M. Jayanthi; C. V. Sairam (Aquaculture International, 2022)

Role of physical oceanography parameters in ocean’s biological response with the passage of cyclone Titli in the Bay of Bengal - K Vijay Prakash; Ch S Geetha Vimala; P V Nagamani; N K Baranval; Shivashankar Manche; T Preethi Latha; I V G Bhavani; Y Umamaheswara Rao; Ch S N Phanindra; K Srinivas; K P Kumari (Journal of Earth System Science, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - K. Vijay Prakash; Ch. S. Geetha Vimala; T. Preethi Latha; Chiranjivi Jayaram; P. V. Nagamani; Ch. N. V. Laxmi (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has affected the entire world and has had a devastating impact on both lives and livelihoods in India. The only way to defeat the rapid spread of COVID-19, is to shut down socio-economic activities and to maintain minimal human interaction with the implementation of a lockdown. Such lockdowns have manifested in a pollution curtailment in almost all spheres of the planet, including in marine pollution. Quantifying this decrease in pollution levels enables the scientific community to assess the contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of the stringent lockdown period (phase 1 and 2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, K d (490), using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for the Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48 and 37.50% in the Chennai and Ennore ports, respectively, due to minimal vessel movement and cargo handling. The stringent lockdown led to the operation of fewer thermal plant units, thus less fly ash was emanated, resulting in a 28.05% reduction in SPM levels over Ennore creek. As industrial and commercial activities subsided, the city’s water bodies became clearer than they were just a fortnight prior to the lockdown, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in K d (490) showed a positive relationship with SPM and thus improved coastal water quality because of the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and reduced levels in particulate matter concentration (PM2.5 and PM10) for the Adyar residential area (24.38 and 28.43%) and for the Nungampakkam commercial area (36.09 and 67.18%) were observed. A significant reduction in PM2.5 concentration (45.63%) was observed in the Ennore-Manali Industrial region.

Additive main effects and multiplicative interaction analyses of yield performance in rice genotypes for general and specific adaptation to salt stress in locations in India - S. L. Krishnamurthy; P. C. Sharma; D. K. Sharma; Y. P. Singh; V. K. Mishra; D. Burman; B. Maji; S. Mandal; S. K. Sarangi; R. K. Gautam; P. K. Singh; K. K. Manohara; et al. (Euphytica, 2021)
The aim of this study was to identify stable rice genotypes tolerant to a salt stress environment and to identify ideal mega-environments using AMMI (additive main effects and multiplicative interaction) stability model analysis. A total of 13 rice genotypes and three salt tolerance checks were evaluated across 13 salt stress locations (alkaline and saline) for the two kharif seasons of 2014 and 2015. Genotype CSR 36 (CHK3) was found to be the most ideal of those tested. Genotypes CHK2 (CST 27) and IR 87952-1-1-1-2-3-B (G05) were found to be the most stable, with above average yields. The check CSR 36 (CHK3) genotype was the best performer in the majority of the environments studied, followed by CSR 27 (CHK2) and IR 87952-1-1-1-2-3-B (G05) which were the best genotypes in the mega-environment consisting of 21 environments evaluated across stress locations and year combinations. Overall, the most promising genotype (IR 87952-1-1-1-2-3-B) had high mean yield and stability and could be used for commercial cultivation or used as donor for breeding programs across salt-affected soils. The genotypes GN13 (IR 87938-1-1-2-1-3-B) and GN11 (IR 87938-1-2-2-1-3-B) showed 60–80% yield advantage at specific salt stress locations, showing that these genotypes could be used for specific environments of salt-affected soils in India.

Trends, causes, and indices of import rejections in international shrimp trade with special reference to India: a 15-year longitudinal analysis - R. Geetha; T. Ravisankar; P. K. Patil; Satheesha Avunje; S. Vinoth; C. V. Sairam; K. K. Vijayan (Aquaculture International, 2020)

Planetary waves in the mesosphere lower thermosphere during stratospheric sudden warming: observations using a network of meteor radars from high to equatorial latitudes - N. Koushik; K. Kishore Kumar; Geetha Ramkumar; K. V. Subrahmanyam; G. Kishore Kumar; W. K. Hocking; Maosheng He; Ralph Latteck (Climate Dynamics, 2020)

Most Efficient Tris(3-Aminopropyl) Amine Based Electron Deficient Tripodal Receptor for Azide - Vanthana Jeyasingh; Kumaresan Murugesan; Sudha Lakshminarayanan; Narayanan Selvapalam; Geetha Das; I. V. Muthu Vijayan Enoch; Lakshminarayanan Piramuthu (Journal of Fluorescence, 2020)

Characterization of future climate extremes over Tamil Nadu, India, using high-resolution regional climate model simulation - Rajadurai Geetha; Andimuthu Ramachandran; J. Indumathi; Kandasamy Palanivelu; G. V. Uma; Prasanta Kumar Bal; Perumal Thirumurugan (Theoretical and Applied Climatology, 2019)

Characterization of inertia gravity waves and associated dynamics in the lower stratosphere over the Indian Antarctic station, Bharati (69.4°S, 76.2°E) during austral summers - N. Koushik; Karanam Kishore Kumar; K. V. Subrahmanyam; Geetha Ramkumar; I. A. Girach; M. Santosh; K. Nalini; M. Nazeer; P. R. Shreedevi (Climate Dynamics, 2019)

Range extension of a bathypelagic squid, Bathyteuthis bacidifera (Cephalopoda: Bathyteuthidae), to the south Arabian Sea with special reference to its age and growth pattern - K. K. Sajikumar; A. I. Arkhipkin; V. Venkatesan; K. M. Jestin Joy; C. P. Binesh; Geetha Sasikumar; Kolliyil S. Mohamed (Marine Biodiversity, 2018)

New camphor hybrids: lipophilic enhancement improves antimicrobial efficacy against drug-resistant pathogenic microbes and intestinal worms - Ramalingam Peraman; Amit K. Tiwari; M. Geetha Vani; J. Hemanth; Y. Geetha Sree; K. Karthik; Charles R. Ashby; Y. Padmanabha Reddy; Raghuveer V. Pemmidi (Medicinal Chemistry Research, 2018)

Anti-tuberculosis drug concentrations in tuberculosis patients with and without diabetes mellitus - A K Hemanth Kumar; V Chandrasekaran; T Kannan; A Lakshmi Murali; J Lavanya; V Sudha; Soumya Swaminathan; Geetha Ramachandran (European Journal of Clinical Pharmacology, 2017)

Assessment of genetic diversity in Clitoria ternatea populations from different parts of India by RAPD and ISSR markers - Ashok Kumar Bishoyi; Vipul V. Pillai; K. A. Geetha; Satyabrata Maiti (Genetic Resources and Crop Evolution, 2014)

Plasma anti-α-galactoside antibody binds to serine- and threonine-rich peptide sequence of apo(a) subunit in Lp(a) - M. Geetha; V. Kalaivani; P. S. Sabarinath; P. S. Appukuttan (Glycoconjugate Journal, 2014)

Expression analysis of drought stress specific genes in Peanut (Arachis hypogaea , L.) - V. Pruthvi; N. Rama; Geetha Govind; Karaba N. Nataraja (Physiology and Molecular Biology of Plants, 2013)

Terrain evaluation through the assessment of geomorphometric parameters using DEM and GIS: case study of two major sub-watersheds in Attapady, South India - V. Prasannakumar; H. Vijith; N. Geetha (Arabian Journal of Geosciences, 2013)

Temporal Trends of Malondialdehyde in Stored Human Plasma - Arun Kumar; B. S. Dhillon; D. N. Rao; Geetha Menon; Hari Shankar; L. K. Dhaliwal; Maiti Leema; Nomita Chandhiok; Neeta Kumar; Rohini Sehgal; Suneeta Mittal; Sumitu Sahdev; et al. (Indian Journal of Clinical Biochemistry, 2012)

Regional Scale Erosion Assessment of a Sub-tropical Highland Segment in the Western Ghats of Kerala, South India - V. Prasannakumar; H. Vijith; N. Geetha; R. Shiny (Water Resources Management, 2011)

Plant regeneration and production of embelin from organogenic and embryogenic callus cultures of Embelia ribes Burm. f.—a vulnerable medicinal plant - A. V. Raghu; Kuzhiyumparambil Unnikrishnan; S. P. Geetha; Gerald Martin; Indira Balachandran (In Vitro Cellular & Developmental Biology - Plant, 2011)

Microwave-assisted rapid extraction of red dye from Caesalpinia sappan heartwood - Shrishailappa Badami; B. Geetha; Sunil V. Sharma; S. Rajan; B. Suresh (Natural Product Research, 2007)

In vitro clonal propagation through mature nodes of Tinospora cordifolia (Willd.) Hook. F. & Thoms.: An important ayurvedic medicinal plant - A. V. Raghu; S. P. Geetha; Gerald Martin; Indira Balachandran; P. N. Ravindran (In Vitro Cellular & Developmental Biology - Plant, 2006)

Effects of presowing treatments, desiccation and storage conditions on germination of Strychnos nux-vomica seeds, a valuable medicinal plant - V. Sivakumar; R. Anandalakshmi; R. R. Warrier; M. Tigabu; P. C. Odén; S. N. Vijayachandran; S. Geetha; B. G. Singh (New Forests, 2006)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Camel Kidney Ferritin: Isolation and Partial Characterization - G. Sobha; S. Suryakala; C. Geetha; V. Deshpande (Veterinary Research Communications, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)